Germany-a movement society?: an investigation of non-activism - Haß, Rabea; Hielscher, Hanna; Klink, Dennis (Journal of civil society, 2014)
Media reports in recent years suggest that Germany has become a movement society. Whenever there is a new infrastructure project (e.g. Stuttgart 21), affected citizens get actively involved in the political process surrounding it—or so it seems. The assumption of existing literature on protest and social movements appears to be true to the ongoing discussion about civic participation. Nevertheless, the current study sheds light on the fact that most affected citizens remain inactive in relation to infrastructure projects in their neighbourhoods. Blame does not lie with the disinterest of the people or their unwillingness to be part of the political process—the opposite is the case. People demonstrate a feeling of moral responsibility to enter the political arena as citizens, but a lack of resources seems to restrain them from doing so. This study shows that, to escape this dilemma, affected citizens hand over the responsibility to existing civic action groups.